“Efecto del corrector foliar (AMICROP Aural PK) en el desarrollo foliar del cultivo de banano (Musa paradisiaca)”. - Palacios Cobeña, Nathaly Mariana (2020)
In Ecuador, bananas are the main export products in the agricultural sector, generating profits for small and large producers that are dedicated to the extensive exploitation of this crop. The lack of macro and micronutrients affects the proper development of the crop. The objective of this research was to establish the effect of the AMICROP AURAL PK foliar corrector on the foliar development in the banana crop. It was carried out at the “Ecuavitro” farm, located in the province of Los Ríos, Canton Buena Fe, in a plantation Banana established by Grand Williams. Four treatments were performed with the proposed leaf corrector versus a control. A completely randomized design (DCA) was used. The phytotoxicity, plant height (cm), pseudostem diameter (cm), leaf emission (%) and leaf width (cm) were evaluated. Similarly, the best dose of the leaf corrector was determined. The proposed application plan caused a 0% phytotoxicity in the Grand Williams banana plants, did not achieve the results expected by the “Ecuavitro” farm. Children from 1.45 to 1.50 cm were selected obtaining an average at 15 days in height of 161.52 cm, in shaft diameter 11.80 cm, in leaf emission 3.3 and in leaf width 19.09. While at 90 days the height was 251.9 cm, in the diameter of the shaft 21.4 cm, the leaf emission 9.54%, and in the width of the blade 26.3 cm. The data collected in the plants on the different doses proposed by the “Ecuavitro” farm did not obtain the expected results.